Pulmonary aspergilloma: surgical outcome of 79 patients in a Moroccan center. (July 2019) - Harmouchi, Hicham; Lakranbi, Marouane; Issoufou, Ibrahim; Ouadnouni, Yassine; Smahi, Mohammed
Background: Pulmonary aspergilloma presents in two clinical and radiological forms: simple and complex aspergilloma. Surgery is the best therapeutic option, most often by anatomic lung resection. Our aim was to report the surgical outcomes according to our experience. Methods: A retrospective study was conducted on data of 79 patients operated on for pulmonary aspergilloma over a period of 10 years. There were 57 (72.15%) men and 22 women (27.84%), with a mean age of 40.45 years. Results: Tuberculosis, all-form combined, was the predominant pathological antecedent in 57 (72.15%) patients, and hemoptysis was the most frequent functional sign in 43 (54.43%). The right side was involved in 39 (49.36%) patients. All patients were operated on via a posterolateral thoracotomy, and an extrapleural plane was necessary in 40 (50.63%). The surgical procedure was a lobectomy in 38 (48.10%) patients and a pneumonectomy in 14 (17.72%). Transfusion of red blood cells was carried out in 10 (12.65%) patients, with one (1.26%) requiring a rethoracotomy for postoperative clotted hemothorax. Two (2.53%) patients presented with empyema after pneumonectomy. The mortality rate was 2.53% (2 patients), and the mean follow-up was 2.5 years. Conclusion: Surgery for pulmonary aspergilloma is associated with a high rate of morbidity and mortality. This surgery has been performed in our department with a very acceptable rate of mortality, especially considering that all patients were operated on by open surgery.